PENGARUH LAPISAN HIDROFOBIK PADA PERMUKAAN ISOLATOR POLIETILEN BERBENTUK SIRIP TERHADAP TINGKAT ARUS BOCOR DAN TEGANGAN FLASHOVER DALAM KONDISI BASAH DAN KERING - Faisal Shidqi; Moch. Dhofir; Tri Nurwati (Jurnal Mahasiswa TEUB, 2023)
This study describes the effect of the hydrophobic coating on the surface of the fin-shaped insulator on the level of leakage current and flashover voltage. The research method used to collect data on leakage current and contact angle directly at the High Voltage Engineering Laboratory of the University of Brawijaya, with the experiment voltage varying between 2 kV, 4 kV, 6 kV, 8 kV, 10 kV, 12 kV, and 14 kV. The experiment begins with determining the value of each insulator, specifically before and after the hydrophobic coating, tested in dry and wet conditions with wetting discharge variations of 10, 30, and 60 mL/s, which corresponds to the trend of rainfall in Indonesia. The study's findings include knowing the level of leakage current in each insulator, particularly when comparing dry conditions and the presence of wet conditions with an increase in wetting discharge so that the surface resistance and power loss caused by the insulator are known. According to the study's findings, the addition of coating reduces leakage current, and the greater the addition of the number of fins, the lower the level of leakage current. Furthermore, the leakage current is affected by the wetting discharge, with the increase in the insulator's level leakage current being directly proportional to the addition of wetting discharge. Keywords — polyethylene isolator, corner contact, hydrophobic, flashover, leakage current, wet and dry conditions